KEPUASAN WISATAWAN SEBAGAI MEDIATOR PROMOSI DAN DAYA TARIK WISATA TERHADAP LOYALITAS WISATAWAN - Budiono Sulistyadi (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2024)
This research examines the influence of promotions and tourist attractions on tourist satisfaction and the subsequent impact on tourist loyalty after the COVID-19 pandemic. Questionnaire using a Likert scale is the research instrument, the respondents are visitors to the Nglanggeran tourist destination. The analysis technique is path analysis which is applied using SmartPLS 3.3.2. This research examines the influence of promotions and tourist attractions partially on tourist satisfaction and tourist loyalty; as well as the influence of promotions and tourist attractions on tourist loyalty through simultaneous tourist satisfaction. The research results show that partially promotions and tourist attractions have an effect on tourist satisfaction, partially promotions have an effect on tourist loyalty but tourist attractions have no effect on tourist loyalty, promotions and tourist attractions through tourist satisfaction simultaneously have an effect on tourist loyalty. Increasing tourist attractions will provide opportunities to increase tourist satisfaction and tourist loyalty.